Industrial policy in the twenty-first century - John Weiss (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Industrial policy has attracted considerable controversy in the development context. This paper makes a case for a pragmatic and limited approach to interventions as a means of stimulating industrialization in the context of current and future challenges facing newly industrializing economies. It begins with a simple definition of industrial policy, a brief survey of the theoretical case, and a taxonomy of different possible interventions. Recent empirical evidence on the role of industrialization in development is examined, whilst considering how far government policy per se has contributed to manufacturing success. Finally, a series of key issues for today's industrializing economies that industrial policy needs to address are highlighted.
Keywords: O14; O25; 330; industrialization; government; trade; protection; productivity; exports; Industrialisierungspolitik